DIGITAL LITERACY IN THE FAMILY ( Case Study of Parenting Patterns in Enforcing Rules on Video Game Consumption ) - Fernando, Erhan Johan; Setyawan , Sidiq (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This study aims to analyze the application of digital literacy in families as an effort to prevent video game addiction in children. The problem of online game addiction is increasing among children, so parents need to play an active role in supervising and guiding the use of digital media. This study employs a descriptive qualitative approach using a case study method on three families with children aged 7–15 years in the Klaten region. Data collection techniques include in-depth interviews and observations, analyzed using the interactive model by Miles & Huberman. The results indicate that each family has distinct communication patterns and media mediation styles when implementing video game consumption rules. Two families (Family 1 and Family 3) showed positive results with a decrease in video game playing intensity after implementing media rules. However, in Family 2, the effectiveness of the rules still faced challenges due to limitations in direct parental supervision. Additionally, the forms of mediation used include restrictive mediation, active mediation, and co-using. The conclusion of this study is that digital literacy within families, implemented through interpersonal communication, supervision, and agreements on digital media use, can serve as a solution to prevent video game addiction in children, provided it is tailored to each family's parenting style and circumstances.